Resolution of inflammation in bone regeneration: From understandings to therapeutic applications. (October 2021) - Newman, Hunter; Shih, Yuru Vernon; Varghese, Shyni
Abstract: Impaired bone healing occurs in 5–10% of cases following injury, leading to a significant economic and clinical impact. While an inflammatory response upon injury is necessary to facilitate healing, its resolution is critical for bone tissue repair as elevated acute or chronic inflammation is associated with impaired healing in patients and animal models. This process is governed by important crosstalk between immune cells through mediators that contribute to resolution of inflammation in the local healing environment. Approaches modulating the initial inflammatory phase followed by its resolution leads to a pro-regenerative environment for bone regeneration. In this review, we discuss the role of inflammation in bone repair, the negative impact of dysregulated inflammation on bone tissue regeneration, and how timely resolution of inflammation is necessary to achieve normal healing. We will discuss applications of biomaterials to treat large bone defects with a specific focus on resolution of inflammation to modulate the immune environment following bone injury, and their observed functional benefits. We conclude the review by discussing future strategies that could lead to the realization of anti-inflammatory therapeutics for bone tissue repair.